Analysis of Differences in Diagnostic Reference Level Based on Size Specific Dose Estimate (JURNAL PROTEKSI KESEHATAN, 2024)
Diagnostic Reference Level (DRL) is the efforts in implementation of radiation protection of medical exposure to X-ray modalities, Computed Tomography scan (CT scan) and general Radiography. Size Specific Dose Estimates (SSDE) is the dose value of an area received by patient in CT examination. Meanwhile, Dose Length Product correction (DLPc) is the total dose received by patient obtained from multiplying SSDE and scan lenght. The purpose was to analyze difference of DRL based on SSDE between manual measurement and indoseCT v.20.b. This research is descriptive quantitative, by collecting head CT DICOM data. The results showed diagnostic reference level of manual measurement was 59.62 mGy (SSDE) and 1492.86 mGy.cm (DLPc). Meanwhile, the DRL of indoseCT v.20.b measurements were 66.65 mGy (SSDE) and 1551.56 mGy.cm (DLPc). There is no significant difference in the DRL based on SSDE from both methods based on statistical tests.  So, the use of indoseCT v.20.b is more recommended because considered faster in determining DRL based on SSDE.